Fanciest doll in the universe eaudiobook - O'Connor, Jane (Fancy Nancy., 2013)
Fancy Nancy is back in New York Times bestselling team Jane O'Connor and Robin Preiss Glasser's picture book Fancy Nancy: Fanciest Doll in the Universe, about the love little girls feel for their favorite dolls—and their favorite sisters! Fancy Nancy's sister, JoJo, can really be a pest sometimes . . . like when she put Easter-egg dye in the kiddie pool and dunked Frenchy in it! But this time she's done something really bad, and Nancy is livid—that's fancy for tres angry and upset. JoJo drew a tattoo on Nancy's precious doll, Marabelle Lavinia Chandelier! Even worse, it's in permanent marker. That means it will never come out! When Mom suggests a fancy doll party to make Nancy feel better, Nancy is excited to accept. But what if the doll drama isn't over? Fans of Fancy Nancy and fancy parties alike will delight in this story of how younger siblings can get on your nerves sometimes, but it always works out in the end. As always, the central theme of all the Fancy Nancy books shines through, showing how Nancy empowers girls with knowledge through her fascination with do-it-yourself fun!